2011
DOI: 10.1002/etc.653
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the causes of oil sands coke leachate toxicity to aquatic invertebrates

Abstract: A previous study found that coke leachates (CL) collected from oil sands field sites were acutely toxic to Ceriodaphnia dubia; however, the cause of toxicity was not known. Therefore, the purpose of this study was to generate CL in the laboratory to evaluate the toxicity response of C. dubia and perform chronic toxicity identification evaluation (TIE) tests to identify the causes of CL toxicity. Coke was subjected to a 15-d batch leaching process at pH 5.5 and 9.5. Leachates were filtered on day 15 and used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…PC has a higher content of N and S; 1.74% and 7.1%, respectively, whereas, BC contains only a trace amount of S (0.07%). The high content of sulfur in PC matches with the previous analyses of Alberta oil sand PC (Puttaswamy and Liber, 2011;Puttaswamy and Liber, 2012).…”
Section: Characteristics Of Bc and Pcsupporting
confidence: 87%
“…PC has a higher content of N and S; 1.74% and 7.1%, respectively, whereas, BC contains only a trace amount of S (0.07%). The high content of sulfur in PC matches with the previous analyses of Alberta oil sand PC (Puttaswamy and Liber, 2011;Puttaswamy and Liber, 2012).…”
Section: Characteristics Of Bc and Pcsupporting
confidence: 87%
“…Previous studies have found coke to leach high concentrations of V into solution upon exposure to water, including process‐affected waters . An 18‐mo lysimeter study found V to leach from coke into solution at concentrations >1000 μg/L, orders of magnitude greater than background concentrations .…”
Section: Introductionmentioning
confidence: 97%
“…Both As and Se are also on the US Environmental Protection Agency's list of priority pollutants (www.epa.gov). Vanadium is a toxic component of the coke leachate produced during the upgrading of bitumen to synthetic crude oil (7 day median lethal concentration, LC 50 < 30% v/v Ceriodaphnia dubia) (Puttaswamy and Liber 2011). Collectively, these elements may help to distinguish natural versus oil sands mining inputs to surface waters.…”
Section: Introductionmentioning
confidence: 99%